Assessing the diagnostic performance of a novel RT-PCR fluorescence method for the detection of human plasmodium species - Melkamu Bedimo Beyene; Seifegebriel Teshome; Yehenew A.; Zewdu Terefework; Antoine R. Stuitje; Tamrat Abebe; Habtamu B. Beyene (PLoS ONE, 2022)
Background Malaria elimination effort is hampered not only by the lack of effective medication but also due to the lack of sensitive diagnostic tools to detect infections with low levels of parasitemia. Therefore, more sensitive and specific high-throughput molecular diagnostic approaches are needed for accurate malaria diagnosis. Methods In the present study, the performance of a novel single-tube MC004 real-time polymerase chain reaction (PCR) assay (MRC-Holland, Amsterdam, the Netherlands) was assessed for the detection of infection and discrimination of Plasmodium species. Blood samples (n = 150) were collected from malaria suspected patients at Adama malaria diagnosis and treatment centre, Adama, central Ethiopia. The positive predictive value (PPV), negative predictive value (NPV), analytical sensitivity and specificity of the assay were assessed against the conventional microscopic method. Results Plasmodium species were detected in 59 (39.3%) of the samples by microscopy and in 62 (41.3%) by the novel MC004 RT-PCR. Plasmodium vivax, Plasmodium falciparum and mixed infections with Plasmodium falciparum & Plasmodium vivax accounted for 47.5%, 40.6% and 11.9% respectively as detected by microscopy. The MC004 RT-PCR assay identified 59.7% and 40.3% of the samples positive for Plasmodium vivax and Plasmodium falciparum respectively. The sensitivity, specificity, PPV, and NPV of the MC004 RT-PCR assay were 95.8%, 97.8%, 92%, and 98.9%, respectively. No mixed infections were detected using the MC004 assay. Conclusion The MC004 RT-PCR assay is a useful tool for the early detection of malaria and identification of Plasmodium species with a high degree of sensitivity and specificity. Due to its high sensitivity, and simplicity (being a single-tube assay), the MC004 is suitable for use in clinical settings and epidemiological studies.